Time-domain thermoreflectance characterization of semiconductor nano/microstructures for power electronic devices - Shabdurasulov, Kirill (Nanyang Technological University, 2023)
Time-domain thermoreflectance (TDTR) is a versatile laser-based pump-probe technique used to measure thermal properties of thin film structures with high accuracy. Parameters of interest are extracted by fitting a simulated thermoreflectance response to the experimentally measured signal. The main research direction of this project is application of TDTR to thermal characterization of nano/microelectronic semiconductor structures for power electronic devices. Thermal boundary resistance (TBR) between layers of materials is one parameter known to be difficult to measure directly. In this project, TDTR is used to extract the TBR values in Al-AlN-Si and Al-AlN-SiC samples. Fundamental aspects of the simulation and experimental design are presented. The standard implementation with a single frequency and modified dual-frequency implementation are presented. It is shown that the dual frequency approach greatly reduces measurement uncertainties. Several limitation are discussed, especially those pertaining to high uncertainties in simulation input parameters. Possible improvements to the technique and future research directions are also presented.